2011
DOI: 10.1002/ibd.21458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of therapeutic drug monitoring of thiopurines in patients with inadequately controlled inflammatory bowel disease

Abstract: Dose-optimization or toxicity-avoidance strategies frequently result from metabolite testing in patients with inadequate efficacy from thiopurines, with evidence of better outcomes. Thiopurine metabolite testing is a potentially powerful tool for optimizing thiopurine usage in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 33 publications
3
108
1
Order By: Relevance
“…18,33 Adequate dosing was defined as doses of 2-2.5 and 1-1.25 mg/kg of azathioprine and as 1-1.25 and 0.5-0.75 mg/kg for mercaptopurine for patients with normal and heterozygote-levels of thiopurine methyltransferase (TPMT) respectively. 6-TGN levels of 100-199 pmol/RBC 9 10 8 were considered low and indicative of partial non-adherence or under-dosing.…”
Section: Thiopurine Metabolite Measurementsmentioning
confidence: 99%
“…18,33 Adequate dosing was defined as doses of 2-2.5 and 1-1.25 mg/kg of azathioprine and as 1-1.25 and 0.5-0.75 mg/kg for mercaptopurine for patients with normal and heterozygote-levels of thiopurine methyltransferase (TPMT) respectively. 6-TGN levels of 100-199 pmol/RBC 9 10 8 were considered low and indicative of partial non-adherence or under-dosing.…”
Section: Thiopurine Metabolite Measurementsmentioning
confidence: 99%
“…A meta-analysis highlighted that patients who achieved clinical remission were more likely to have levels of 6-TGN >230-260 pmol/8×10 8 red blood cells compared with patients who had persistently active disease (62% vs. 36%, respectively) ( 65 ). A small randomized trial suggested that antimetabolite dose modifi cation based on metabolite determination was not superior to simple weight-based dosing ( 66 ); however, other more recent evidence suggests that the use of metabolites can benefi t clinicians who are treating IBD patients with antimetabolites ( 67,68 ). Th e current role of TGN measurement remains controversial and is further complicated by inconsistent coverage and availability.…”
Section: Azathioprine/6-mercaptopurinementioning
confidence: 99%
“…There are reports of enhanced efficacy of azathioprine when dosage is increased in response to 'sub-therapeutic' 6-TGN concentrations in patients not in remission, but again such studies have used retrospective data. 7,10 Second, weight-based estimates of dosing in conjunction with regular tests for hematological and hepatic toxicity have been used successfully for many years. The use of surrogate markers of therapeutic dosage, such as a rise in mean corpuscular volume 11 and reduced total lymphocyte count, has assisted clinicians by reassuring them that the thiopurines dose is adequate.…”
mentioning
confidence: 99%
“…Clinicians are often timid in pushing the dose of thiopurines on the basis of the patient's weight, as retrospective and prospective studies of clinical practice have shown, 12,13 and weight-based dosage correlates poorly with 6-TGN concentrations. 10,14,15 It is not unusual for sub-therapeutic dosing on the basis of the patient's weight to be associated with therapeutic 6-TGN concentrations. The metabolite algorithm would suggest that increasing the dose and waiting for efficacy or toxicity to occur might waste valuable time in patients with ongoing active disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation